2017
DOI: 10.1016/j.jhep.2016.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporin derivatives inhibit hepatitis B virus entry without interfering with NTCP transporter activity

Abstract: In this study, we identified new compounds that selectively inhibited hepatitis B virus (HBV) entry, and did not impair bile acid uptake. Our evidence offers a new strategy for developing anti-HBV drugs with fewer side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
88
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 51 publications
(94 reference statements)
0
88
0
2
Order By: Relevance
“…Other drugs already in use that block the in vitro interactions of HBV with NTCP include the immunomodulatory agent CyclosporinA, anti-retroviral ritonavir, ezetimibe (cholesterol lowering) and irbesarten (anti-hypertensive angiotensin II receptor antagonist) [178] . Recent studies have identified new small molecules (derivatives of CyclosporinA) which are able to inhibit HBV viral attachment, without impairing the NTCP-dependent uptake of bile acids, suggesting that these functions may be separated [179] .…”
Section: Treatmentmentioning
confidence: 99%
“…Other drugs already in use that block the in vitro interactions of HBV with NTCP include the immunomodulatory agent CyclosporinA, anti-retroviral ritonavir, ezetimibe (cholesterol lowering) and irbesarten (anti-hypertensive angiotensin II receptor antagonist) [178] . Recent studies have identified new small molecules (derivatives of CyclosporinA) which are able to inhibit HBV viral attachment, without impairing the NTCP-dependent uptake of bile acids, suggesting that these functions may be separated [179] .…”
Section: Treatmentmentioning
confidence: 99%
“…Currently, primary human hepatocytes (PHHs) (Lempp et al, 2017;Ni and Urban, 2017;Shimura et al, 2017), HepaRG cells (Gripon et al, 2002;Schulze et al, 2012), and primary tupia hepatocytes (PTHs) (Kock et al, 2001;Ren and Nassal, 2001) are the main cell models used to study the early steps of HBV infection. PHHs, the natural host of HBV, are regarded as the ideal cellular model for HBV infection.…”
Section: Introductionmentioning
confidence: 99%
“…129 The inhibition of NTCP by these inhibitors normally will result in the loss of transporter function of NTCP, leading to the inhibition of bile acid uptake, which might cause unwanted adverse effects. Interestingly, Shimura et al 130 derivatives with anti-HBV activity in vitro via direct interaction with NTCP to inhibit viral attachment. These compounds inhibited multiple HBV genotypes including one clinically relevant nucleoside analog-resistant HBV isolate.…”
Section: Sodium Taurocholate Cotransporting Polypeptidementioning
confidence: 99%